Qualidade de vida e qualidade de vida no trabalho de docentes universitários - Sanchez, Hugo Machado (2015)
The objectives of this study were to analyze the quality of life (QOL) and the quality of working life (QWL) of university professors in different areas of knowledge; identify the influence of socio-demographic aspects of QOL and QWL university teachers; analyze the effect of aspects to work on QOL and QWL academics and identify the influence of aspects related to health in QOL and QWL academics from different fields of knowledge. Cross-sectional study in a university in Brazil midwestern, whose data were collected by sociodemographic questionnaire with questions related to job data and health, the WHOQOL-Bref to evaluate QOL and TQWL-42 for analysis of QWL of 284 academics from the fields of science health / biology, agricultural sciences, humanities and exact sciences. The results of QOL and QWL did not differ between areas of knowledge and were influenced by factors such as, are they better pay (p = 0.017), the statutory agreement (p = 0.005) did not move from the city of residence for act as teachers (p = 0.049), better lighting (p = 0.000), comfortable temperature (p = 0.001), few noise (p = 0.048), material resources (p = 0.042), fewer students in class (p = 0.027) and exercise workload in administrative function (p = 0.023). It was also observed that QOL and QWL are interrelated (r = 0.564 and p = 0.000). Perform administrative activities, number of students in the classroom are predictors respectively QOL and QWL. It was found that teachers who practice physical activity had better scores on the QOL (p = 0.006) and in the QWL (p = 0.003) and those who reported a better quality asleep (p = 0.001). In addition, QOL and QWL also had lower scores on teachers who reported sick leave (p = 0.023), those who make use of medication (p = 0.034), which have poor diet (p = 0.000) and have less leisure activities (p = 0.001) and there was an association between age and QOL (r = 0.119 and p = 0.045). It concludes that the work and life of teachers are interdependent and there is no difference in QOL and QWL among teachers of different areas of knowledge. Besides the evaluated teachers showed that their QOL and QWL are influenced by organizational factors / work-related and health aspects.